IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BOLAANG MONGONDOW UTARA - SAMPOH, VIVI; RURU, JOORIE; PALAR, NOVIE (Sam Ratulangi University, 2019)
The purpose of this study was to find out how the implementation of the Population Administration InformationSystem (SIAK) policy in the Population and Civil Registration Office of North Bolaang Mongondow Regency.The studyuses a descriptive-qualitative approach. The focus of research is the four dimensions of public policy implementation,namely communication, resources, disposition, and bureaucratic structure. The research informants were the head of thedepartment, the heads of fields, staff / implementing staff, and the community served. Data collection uses interviewguidelines, while the analysis technique used is the analysis of interactive models from Miles and Hubernann.Based onthe results of the study concluded: (1) Communication is carried out well and effectively. SIAK's policies are disseminatedto the public both directly and through the assistance of sub-district governments and village governments, throughinformation boards in the Office, and through brochures or leaflets, electronic media such as websites, internet sites. (2)Human resources for the implementation of SIAK policies are inadequate in quantity; but the quality is good enough.Financial resources for the implementation of SIAK are sufficient to be seen from the funds / operational costs allocated;but work facilities and infrastructure are still inadequate for the implementation of SIAK in prime. (3) Disposition(employee attitude) in implementing SIAK policies is quite good seen from commitment, consistency, honesty, anddemocratic attitude in carrying out services with the SIAK system. (4) The bureaucratic structure in implementing theSIAK policy has been well organized and effective. SOP (Standard Operating Procedure) and organizational structure anddivision of labor.Keywords: policies, population administration information systems